Country music [compact disc, unabridged] - Duncan, Dayton; Burns, Ken, 1953- (Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2019)
A companion to the 2019 PBS mini-series honoring America's most popular music and the artists who shaped twentieth-century history and culture explores the music's roots, growth, styles, and commercial success.